Potential growth inhibition of freshwater algae by herbaceous plant extracts - Nurhaida binti Kamaruddin (Tanjong Malim, 2019)
Potential growth inhibition of freshwater algae by herbaceous plant extracts by Nurhaida binti Kamaruddin